Polymers for Food Applications - Gutiérrez, Tomy J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book presents an exhaustive review on the use of polymers for food applications. Polymer-based systems for food applications such as: films, foams, nano- and micro-encapsulated, emulsions, hydrogels, prebiotics, 3D food printing, edible polymers for the development of foods for people with special feeding regimes, sensors, among others, have been analyzed in this work. About the Editor: Dr. Tomy J. Gutiérrez has a degree in chemistry (Geochemical option) from the Central University of Venezuela (UCV) (December, 2007), a degree in education (Chemical mention) from the same university (UCV, July, 2008), has a specialization in International Negotiation of Hydrocarbons from the National Polytechnic Experimental University of the National Armed Force (UNEFA) - Venezuela (July, 2011). He also has a Master's and PhD degree in Food Science and Technology obtained in October, 2013 and April, 2015, respectively, both from the UCV. It has also PhD studies in Metallurgy and Materials Science from the UCV and postdoctoral studies at the Research Institute in Materials Science and Technology (INTEMA). Dr. Gutiérrez has been a professor - researcher at the UCV both at the Institute of Food Science and Technology (ICTA) and the School of Pharmacy at the same university. It is currently an adjunct researcher in the INTEMA - National Scientific and Technical Research Council (CONICET), Argentina. Dr. Gutiérrez has at least 20 book chapters and 40 publications in international journals of high impact factor. Dr. Gutiérrez today is developing a line of research in nanostructured materials based on polymers (composite materials), which are obtained on a pilot scale to be transferred to the food, pharmaceutical and polymer industry. In addition, it is a collaborator of international projects between Argentina and France, Brazil, Venezuela and Colombia.
Polymers for food applications - News -- Edible films -- The potential of vegetal and animal proteins to develop more sustainable food packaging -- Properties of micro- and nano-reinforced biopolymers for food applications -- Recent trends on nano-biocomposite polymers for food packaging -- Surface properties of biodegradable polymers for food packaging -- Transport phenomena in edible films -- Antimicrobial films and coatings incorporated with food preservatives of microbial origin -- Postharvest application of biopolymer-based edible coatings to improve the quality of fresh horticultural produce -- Edible foams stabilized by food-grade polymers -- Foams for food applications -- Biodegradable foams in the development of food packaging -- Composite foams made from edible and biodegradable polymers for food packaging applications -- Nano and microencapsulation using food grade polymers -- Food-grade biopolymers as efficient delivery systems for nutrients: An overview -- Current processing methods in the development of micro- and nanoencapsulation from edible polymers -- Biopolymers for the nano-microencapsulation of bioactive ingredients by electrohydrodynamic processing -- Food gel emulsions: structural characteristics and viscoelastic behavior -- Polymers for structure design of dairy foods -- Partially hydrolyzed guar gum: preparation & properties -- Development of hydrogels from edible polymers -- Food grade polymers for the gelation of edible oils envisioning food applications -- Current applications in food preservation based on marine biopolymers -- Functional carbohydrate polymers - Prebiotics -- Role of different polymers on the development of gluten-free baked goods -- 3D Food Printing - Perspectives -- Sensors based on conducting polymers for the analysis of food products.
Keywords: Food science; Chemistry, Organic; Food Science; Organic Chemistry